Initial Reforms Implemented In The Court System In The Republic Of Uzbekistan - Makhkamov Abdikayum Makhkamovich (Academia One Publishing, 2024)
This article provides information on further improvement of the judicial system, advanced training of judges and court employees, new methods used in the selection and training of personnel.
Keywords: Judicial system; personnel policy